Sea water stress affects mitochondrial proline oxidation but not alternative oxidase activity in durum wheat germinating seedlings - Laus M.N.; Flagella Z.; Trono D.; Soccio M.; Di Fonzo N.; Pastore D. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
The mitochondrial defence mechanisms may contribute to depict a durum wheat plant ideotype showing higher water use efficiency under water and/or salt stress and able to be irrigated with brackish water. In particular, two important mitochondrial mechanisms involved in resistance to environmental stresses are: (i) the inhibition of proline oxidation and (ii) the control exerted by Alternative Oxidise (AOX) of harmful reactive oxygen species generated under stress. Durum wheat mitochondria (DWM) from early seedlings were used to study these physiological mechanisms under salt stress. Seedlings were germinated both in distilled water and in two different diluted sea water solutions, leading to either moderate or severe damage to growth. To assess the contribution of the osmotic component of stress (water stress), a parallel investigation was performed by using hyperosmotic mannitol solutions. Comparison of proline and succinate oxidation by DWM showed that early inhibition of proline oxidation should be considered a mitochondrial adaptation to stress rather than a damage to oxidative properties, while, under our experimental conditions,no increase in AOX activity under stress was observed. In conclusion, early inhibition of proline oxidation may be a useful character enhancing tolerance to salt and water stress in durum wheat.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)